Implementasi Teori Kognitif dalam Mengembangkan Karakter Siswa SD Kelas I Berbasis Dimensi Bernalar Kritis - Liliani, Liliani; Gede Astawan, I (Journal of Comprehensive Science, 2024)
This study aims to test the effectiveness of the application of cognitive theory in developing the character of grade I elementary school students based on the dimension of critical reasoning. This study uses a qualitative approach with a type of classroom action research (PTK) involving 20 students in grade I of SD Negeri 005 Bentian. Data collection is carried out through observation, interviews, and tests. The results showed that students who learned using cognitive theory were more active, enthusiastic, and able to apply character values in daily life compared to students who learned using traditional approaches. Students who learn to use cognitive theory also show a deeper understanding of character values and better critical thinking abilities. This study concludes that the application of cognitive theory in character learning can improve the character of elementary school students in grade I based on the dimension of critical reasoning.